Clinical features and treatment outcomes of visceral leishmaniasis patients admitted to three centers in Oromia, Ethiopia - Samson Tekalign; Cherinet Adera; Margriet den Boer; Hirpha Miecha; Ashenafi Zewde; Dagnachew Mulugeta; Tesfahun Bishawu; Weyuma Birru; Awoke Lema; Tilahun Sahlu; Fabiana Alves; Marcel Manzi; et al. (Journal of Infection in Developing Countries)
Introduction: In three health care facilities in the Oromia region, the aim of this study is to report on 1) the number of VL cases registered over time (2013-2018) and 2) the clinical profile, type of treatment used and response to treatment.